MODEL KURIKULUM SISTEMATIK DAN RADIKAL - Sari, Zuyyina Linda; Kudsiyeh, Kudsiyeh; Asrori, Sholi; Zaironi, Muhammad (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2026)
This study aims to examine in depth the concepts of systematic and radical curricula and their relevance to the development of Islamic Religious Education (PAI). Using qualitative methods with a library study approach, this study examines various literature on curriculum theory, critical education, and PAI development. The results of the study indicate that systematic consistency in learning planning is structured, tiered, and focused on measurable objectives. This model is relevant for PAI because it can ensure material continuity, clarity of learning objectives, and evaluation that covers cognitive, affective, and psychomotor aspects. In contrast, the radical curriculum is omitted in critical education, which positions students as active subjects, encourages dialogue, reflection, and contextual reading of social reality. In the context of PAI, the radical approach contributes to the formation of critical awareness, moderate attitudes, and students' ability to actualize Islamic values ​​​​relevant to the challenges of the times. This study concludes that both models have different characteristics and strengths but complement each other. The integration of systematic and radical curricula is seen as an ideal strategy for building a PAI curriculum that is strong in value, adaptive, critical, and oriented towards strengthening students' character.